High Resolution Computed Tomography findings and Computed Tomography severity index in COVID-19 Infection Correlated with Age and Gender - Sharma, Prakash; KC, Subash; Gyawali, Merina; Karki, Dipesh; Shrestha, Ashish; Pun, Benju Tilija; Pokhrel, Amrit (Nepalese Journal of Radiology, 2021)
Introduction: The new coronavirus disease -19 (COVID-19) is caused by SARS-CoV2 strain of coronavirus. The Computed tomography (CT) severity index is a scoring system used to assess the lung changes and involvement by COVID-19 based on approximate estimation of pulmonary involved areas. This study was done to identify the spectrum of CT chest findings and CT severity index in COVID-19 infection and its correlation with age and gender. Methods: Patients with COVID-19 infection with positive PCR results and positive pulmonary CT findings were included in the study. All these patients underwent high-resolution computed tomography (HRCT) of the chest. The CT scan severity score in all of these patients was calculated and the results were analyzed by SPSS version 21. Results: A total of 104 patients with confirmed COVID-19 infection were included in this study. There were 59 males (56.73%) and 45 females (43.3%) in this study. There was a higher chest severity score in males compared to females. However, there was no significant correlation between the age and CT chest severity score. Conclusion: HRCT chest can help in the early identification of the patients who need intensive care. Early admission and intensive care of the patients with high CT severity scores may help to reduce the mortality of COVID-19 patients.